2018
DOI: 10.1093/ehjcr/yty146
|View full text |Cite
|
Sign up to set email alerts
|

Killing two birds with one stone—MitraClip for flail P2 and systolic anterior motion of mitral valve: a case report

Abstract: BackgroundThe MitraClip system has been used extensively in high-risk patients with severe degenerative mitral regurgitation (MR). Recent reports have demonstrated the feasibility of using the MitraClip device to treat systolic anterior motion (SAM) of the mitral valve in obstructive hypertrophic cardiomyopathy (HOCM).Case summaryWe report the case of a 76-year-old lady who had both symptomatic severe degenerative MR and HOCM that were refractory to medical therapy. Both pathologies were treated successfully u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…While a higher prevalence of chordal rupture (5.4%) has been reported in a small surgical series (12), a larger cohort of HCM patients showed that chordal rupture is a rare event in HCM (1%) (11). From a literature search, we found 26 cases of HCM with ruptured chordae tendineae (Table 1) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Etiopathogenesismentioning
confidence: 85%
“…While a higher prevalence of chordal rupture (5.4%) has been reported in a small surgical series (12), a larger cohort of HCM patients showed that chordal rupture is a rare event in HCM (1%) (11). From a literature search, we found 26 cases of HCM with ruptured chordae tendineae (Table 1) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Etiopathogenesismentioning
confidence: 85%
“…10,11 It has an association with hypertrophic obstructive cardiomyopathy due to the MV being more susceptible to positioning within the LVOT. Wong et al 12 report the effectiveness of MitraClip in the management of MR and SAM in the setting of hypertrophic obstructive cardiomyopathy. Despite the isolated basal septal hypertrophy and marked SAM of the MV, the patient was not noted to have significant LVOT obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Several small studies have investigated the transcatheter MV EE procedure (MitraClip) in the setting of HOCM, to reduce SAM and LVOT obstruction. [39][40][41] Although these studies were limited by size and adequate follow-up, the use of Mitraclip is a potential therapeutic option in symptomatic HOCM patients who are not surgical candidates and/or do not have optimal coronary (septal perforator) anatomy for alcohol septal ablation.…”
Section: Future Perspectivesmentioning
confidence: 99%